Transforming Students' Mathematical Skills with JKT 48 Songs - anggraeni, Nanda Ayu; Choirudin, Choirudin; Ningsih, Eka Fitria; Darmayanti, Rani; Dhakal, Amrit (CV. Bimbimbingan Belajar Assyfa, 2024)
Students' mathematical communication skills are crucial for supporting conceptual understanding and problem solving in mathematics. However, many students still experience difficulties in relating mathematical ideas to everyday situations and clearly explaining mathematical concepts and relationships. This study aims to test the effectiveness of the Auditory Intellectually Repetition (AIR) learning model combined with the JKT 48 song